Belacqua and the “I” in the Novellas – the Narration of Two Worlds in the Prose of Samuel Beckett - Gonçalves, Livia Bueloni (ABEI Journal, 2011)
Based on the analysis of excerpts from Samuel Beckett´s first bookof short stories, More Pricks than Kicks (1934), this article investigates towhat extent the narrator in this book demonstrates certain  characteristics that appear in subsequent prose by Beckett, mainly as regards to interventions in the stories that are told. To discuss this subject, excerpts will also be used from “Premier Amour” (1970),which, together with “L’Expulsé”, “Le Calmant” and “La Fin” (1955), make up the first fictional texts written by Beckett in French.The importance of comparing such stories to those from More Pricks thanKicks comes from the fact that they present the typical Beckettian first-person narrator, well-known for his peculiar story-telling style, replete with impasses and questions about the narrated story. Comparison between the narrative styles in these texts also allows us to investigate the characteristics of two distinct and unique moments in Samuel Beckett´s prose.